Science, Technology, Engineering, and Mathematics-Based Problem-Based Learning Model for Fifth-Grade Students’ Learning Outcomes in Perimeter and Area of Plane Figures - Meiliza Aulia; Yarisda Ningsih (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the effect of science, technology, engineering, and mathematics-based problem-based learning model on students’ learning outcomes in perimeter and area of plane figures in fifth-grade elementary school. The study focuses on comparing learning outcomes between students taught using science, technology, engineering, and mathematics -based problem-based learning model and those taught using conventional learning methods. Methodology: This study used a quantitative approach with a quasi-experimental method and nonequivalent control group design. The sample consisted of 49 fifth-grade students selected using purposive sampling. Data were collected using pre-test and post-test instruments. Data analysis was conducted using IBM SPSS Statistics 25, including normality, homogeneity, and Mann–Whitney U tests. Main Findings: The results showed that the average post-test score of the experimental class was higher than the control class. The Mann–Whitney U test indicated a significance value of 0.013 < 0.05, showing a significant difference. This indicates that the science, technology, engineering, and mathematics -based PBL model has a significant effect on improving students’ learning outcomes in mathematics. Novelty/Originality of this study: This study highlights the application of science, technology, engineering, and mathematics-based PBL specifically on perimeter and area of plane figures in elementary school context. It provides empirical evidence of its effectiveness in improving learning outcomes and offers a contextual and student-centered learning approach, contributing to the development of innovative mathematics learning models at the primary education level.